City Government of Surabaya’s "Peken" E-Commerce Application from the Perspective of Maqashid Syariah - Rachman, Rio Febriannur; Wahyuningsih, Mirotin Eka (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This study aims to analyze the implementation of the Peken e-commerce program run by the Surabaya City Government, reviewed from the perspective of Maqasid Syariah popularized by Ibn Asyur and the Sustainable Development Goals (SDGs) outlined by the United Nations (UN). Peken is a digital economic innovation designed to empower local MSMEs, increase their competitiveness in the digital market, and support sustainable economic development. This study uses a qualitative method with a literature study approach to explore the relevance and suitability of Peken policies with the principles of Maqasid Syariah and SDGs. Based on the perspective of Maqasid Syariah, the Peken program is in line with the maintenance of wealth (hifzh al-mal), life (hifzh an-nafs), and public welfare (al-maslahah al-‘ammah). This program not only provides wider economic access for MSMEs, but also creates economic and social stability for the lower classes in Surabaya. From the SDGs perspective, “Peken” supports no poverty (SDG 1), decent work and economic growth (SDG 8), and reduced inequality (SDG 10). The results of the study show that the implementation of Peken supports both sharia and global development goals by providing an inclusive and sustainable platform for MSMEs, strengthening local economic growth, and providing broad social benefits. This study emphasizes the importance of integrating digital economic policies with ethical values ​​and sustainable development to achieve overall community welfare